Protocol for conducting a scoping review on the influence of low-stakes assessment on student learning in medical education [version 1; peer review: 2 approved] - Mohi Eldin Magzoub; Carvalho Filho; Susan Waller; Lamburt Schuwirth; Imran Zafar (F1000Research)
Rationale and Background Low-stakes assessments enhance student learning outcomes by providing a comprehensive view of performance and promoting competency-based education. Multiple low-stakes assessments encourage continuous learning and incorporate formative feedback for a realistic and long-term environment. Diverse assessment methods ensure psychometric rigor, utility and a programmatic assessment approach with multiple data points affording high-stakes decisions on progression. Objective This scoping review aims to systematically identify and map existing literature on the use of low-stakes assessments in medical education and determine their impact on student learning outcomes in terms of, motivation and engagement achievements/competencies. Methods and Analysis The review will use the Joanna Briggs Institute’s framework for scoping review studies, searching eight databases and grey literature. A presearch will be done in PubMed, Scopus, and Google Scholar using terms related to low-stakes assessment, formative assessment, continuous assessment, and programmatic assessment within the context of medical education. The Covidence Systematic Review tool will aid in screening and conflict resolution. The reference lists of included studies will be checked manually for other relevant literature. Two research team members will independently screen and extract data, resolving discrepancies with a third team member. Inclusion and exclusion criteria will be refined iteratively based on key research themes. The review will follow PRISMA-P guidelines, focusing on the impact of low-stakes assessment on student learning in medical education. Ethics and dissemination No ethical approval is required as all data will be collected from published and grey literature. Findings will be disseminated at relevant conferences and submitted for publication in peer-reviewed journals.